The Impact Of The Program Indonesia Pintar, School Operational Assistance, Special Allocation Fund And Gross Regional Domestic Product On Gross Enrollment Rate In 34 Indonesian Provinces 2020-2023 - Martha Carolina; Jesly Panjaitan; Tio Riyono (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
Education is a key pillar of human resource development; however, the achievement of the Gross Enrollment Rate (GER) in Indonesia still faces challenges, particularly at the secondary level. This study analyzes the effects of the Program Indonesia Pintar (PIP), Bantuan Operasional Sekolah (BOS), Dana Alokasi Khusus (DAK) in the education sector, and Gross Regional Domestic Product (GRDP) per capita on the GER across 34 Indonesian provinces from 2020 to 2023. Panel data regression was employed, with the best model selected through Chow, Hausman, and Lagrange Multiplier tests, and the Random Effect Model (REM) used for estimation. The results reveal that GRDP per capita consistently exerts a positive and significant influence on the GER at all education levels, highlighting the importance of regional economic capacity in expanding educational access. The PIP shows a significant positive effect at the junior high school level but no significant impact at the elementary or senior high/vocational levels. BOS funds exhibit no significant effect across all levels, while DAK shows a negative and significant effect at the junior high level. The COVID-19 pandemic also had a significant impact, reducing overall enrollment ratios but slightly increasing participation at the elementary level. These findings emphasize the need for more contextual and adaptive education policies that align with regional economic capacities and program implementation effectiveness.